Large wood debris contributes to beach ecosystems but colombian beachgoer’s do not recognize it (2022)
Large Woody Debris (LWD) accumulation serves essential ecological functions and benefits society’s coastal ecosystems (e.g., beaches). Thus far, the ecosystem services perspective has paid little attention to LWD. Therefore, we aim to contrast social perceptions on LWD and its ecological significance in Puerto Velero beach, Caribbean, Colombia. In consequence, the contribution of LWD to the conformation and creation of Puerto Velero beach was analyzed, as well as how beachgoers perceive the importance of LWD and if they were willing to pay to remove LWD in this beach. To achieve this, a quantitative convergent approach was then proposed using GIS analysis and remote sensing to understand the contributions of LWD to the Puerto Velero beach ecosystem; and in addition, a survey was performed to determine how beachgoers perceived LWD and how they valued the phenomenon. Results indicate that LWD contributed to beach maintenance; nevertheless, most people neglected LWD values because of its lack of visual attractiveness. As such, ecosystem services targets become conflicted because people positively perceived ecosystem services provided by beaches, but they did not assign importance to the beach dynamics they deemed unattractive, regardless of their vast importance.